Pertanggungjawaban Pidana terhadap Warga Negara Asing yang Melakukan Tindak Pidana Penganiayaan - Made Dwi Kurnia Dananjaya; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2020)
Indonesia in this era of globalization was made as a country that can include foreigners in carrying out activities in the form of industry, tourism and commerce in Indonesia. The development of technological science, allows people to be more consumptive in using it. Viewed from a psychological perspective, it is often found that foreign tourists have deviant behavior from legal norms that exist in Indonesia. One of the deviant acts is the criminal treatment of persecution of a foreign citizen to Indonesian citizens who are in the Republic of Indonesia. There is also a problem statement. The purpose of this study is to determine criminal liability and criminal sanctions given to foreign citizens who commit criminal acts of persecution. This study uses a normative method because there are still vague norms, based on the opinions of legal scholars and the Law. One person can have a personality in criminal liability if some things or actions made by someone in violating positive law, if one can eliminate the sense of responsibility in someone who found an element of a person's ability to lose responsibility.